Javier Lasso de la Vega and the principles of bibliographic cataloging - López Guillamón, Ignacio (Revista General de Información y Documentación, 2012)
Showing cataloging principles prepared by J. Lasso de la Vega, as the foundations of an international cataloging code. It discusses the Cataloguing Principles in Paris (1961) and the International Cataloguing Principles (2009), proposed by the IFLA. It highlights the value of such sets of theoretical literature own cataloging in the creation of catalogs and bibliographies to represent creations uniquely faithful and intellectual, practical and artistic men, and to communicate knowledge, in the double sense of giving and receiving information. We conclude that in the course of the principles of bibliographic cataloging, the figure of J. Lasso de la Vega should have a role commensurate with its responsibility to formulate in 1950 cataloging principles which form the theoretical basis for an international cataloging code. It is emphasized that this Spanish author and his work cataloging suffer from a study that highlights their contributions to the theory of cataloging.